Opposition of the Natural and the Artificial in the Fictional World of Georges Sand: Doll, Puppet, Automaton - Anna V. Popova (Studia Litterarum)
The article deals with the image of the doll and peculiarities of the opposition ‘living — lifeless’ concerned with this image in the works of George Sand. In her autobiographical texts and memoirs, the author reflects on the educational and gender potential of the doll. At the same time, she counterpoises a traditional doll with a mechanical one, emphasizing the contrast of the natural and the artificial in the given opposition. In this case, the criterion is the state of being programmed, the predictability of the automaton that excludes the chance of game improvisation. The doll “comes to life” only when the human’s creative energy fills the spiritual void of its shell, imparting some individual features to it. An obvious example of such unity is a puppet. The doll as a theatrical attribute appears in the novel of George Sand L’Homme de Neige (1859) and also in her article “Le Théâtre des marionnettes de Nohant” (1876). In the novel, one of the Italian puppet theatre characters named Stenterello, the Florentine analogue of Pulcinella, creates significant opportunities for self-identification for the main character who is striving to unravel the mystery of his origin. In the article, the opposition “natural — artificial” acquires aesthetic sense, and it is interpreted in the course of the correlation of truth and fiction in art. Rough and primitive glove puppets — burattini — come to life in the puppeteer’s hands, acquiring individual features, while automatons, though skilfully imitating living humans, are lifeless because of their mechanical autonomy. The symbiosis of a person and a doll in the works of George Sand becomes a metaphor for creative work that brings into existence artistic images which represent an inseparable unity of creator and her creation.